Correction of Air Buoyancy on E0-74 Mass Measurement with Pt-Ir K-112 Standard - Zuhdi Ismail; Renanta Hayu Kresiani (Universitas Sebelas Maret, 2021)
Determination of the mass value of E0 no 74 by calibrating it using the Pt-Ir standard has high complexity. This is caused by a significant difference in the density of standards. In this study, the E0 no 74 made of stainless steel has a density of 8.051.130 kg.m−3 calibrated by a mass standard of Pt-Ir which has a density of 21.552.940 kg.m−3. By Archimedes' law, the buoyant force generated by the air due to this density difference is huge. Therefore, the correction of air buoyancy is very important. The air buoyancy correction value is obtained by determining the air density using the CIPM-2007 formula. The correction that arises due to air buoyancy while weighing in the air is -0.00115 g and is greater at higher density. The implication of buoyancy correction is identified by analyzing the equivalence of the measurement result using a reference value from the calibration certificate issued by BIPM. The measurement result is equivalent if -1<En<1. The value for the corrected mass is -0.078.